Environmental value of dung in mixed crop-livestock systems* - DIKSHIT, A K; BIRTHAL, PRATAP S (The Indian Journal of Animal Sciences, 2010)
Dung is an important byproduct of livestock. It is used as manure, or is converted into dung cakes for use as fuel or mixed with clay for flooring and plastering of mud houses. Apart from these important uses of dung, it also has a great environmental value. Its contributions to environment could be positive as well as negative. From the negative side, methane emission from manure management is a negative environmental externality. The positive externality is the use of dung cake as domestic fuel, which can be seen as a substitution or replacement of the equivalent amount of thermal energy from fuel-wood or fossil-fuel. It is a great saving on fuel-wood by cutting down of standing forests and trees, and another is the saving of land that is required to produce replacement amount of fuel-wood for dung cake. In the present paper we have estimated the quantity of fuel-wood that would be required to replace dung-cake as domestic fuel, and the land area that would be required to produce or supply that amount of fuel-wood. At current feeding rates, India produces over 83 million tonnes of dry dung-cake, which is used annually by the rural households as domestic fuel for cooking and warming. If this amount of dung cake was to be replaced by fuel wood, the country will require producing an additional amount of 23.5 million tonnes of fuel-wood, and the additional land requirement for fuel-wood plantation will be about 2.35 million ha. From the perspective of food production, supposing that under traditional rainfed agriculture food grains yield ranges from 1.5 to 2 tonnes/ha, the land saved would produce 3.5 to 5 million tonnes of foodgrains.